2013
DOI: 10.4314/wsa.v39i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen, testosterone, cytotoxin and cholinesterase inhibitor removal during reclamation of sewage to drinking water

Abstract: Namibia is the driest sub-Saharan country in Africa. Namibia's capital, Windhoek, reclaims sewage water for domestic use at the Goreangab Water Reclamation Plant (GWRP). Risks associated with sewage effluent and reclaimed sewage should be closely monitored; therefore water at the Gammams Sewage Treatment Plant (GSTP) inlet and outlet, as well as reclaimed water from the GWRP, were assayed using selected bioassays. Samples collected were analysed using enzyme-linked immunosorbent-assays and chromogenic tests fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Furthermore, excess sewage effluent from the GSTP, which receives stormwater runoff and domestic sewage, is also released into the dam. This effluent showed AChE inhibition of up to 22% (Faul et al 2013). Comparable studies indicated that sewage effluent and stormwater runoff can be a source of chemicals (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, excess sewage effluent from the GSTP, which receives stormwater runoff and domestic sewage, is also released into the dam. This effluent showed AChE inhibition of up to 22% (Faul et al 2013). Comparable studies indicated that sewage effluent and stormwater runoff can be a source of chemicals (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, part of the effluent from the Gammams sewage treatment plant (GSTP) is released into the dam. This effluent contains testosterone concentrations exceeding 10 pg ml -1 (Faul et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations